The rate of DNA synthesis in ovaries, fat body cells, and pericardial cells of the bumblebee (Bombus terrestris) depends on the stage of ovarian maturation - Zavodska, Radka; Sehadova, Hana (Frontiers in physiology, 2023)
Bumblebees are important pollinators of plants worldwide and they are kept for commercial pollination. By studying the process of oogenesis, we can understand their ontogenetic developmental strategy and reproduction. We describe the anatomy of the ovary of the bumblebee Bombus terrestris using 3D reconstruction by confocal microscopy. We found that an oocyte is accompanied by 63 endopolyploidy nurse cells. The number of nurse cells nuclei decreased during oogenesis and the cells are finally absorbed by the oocyte. We monitored the rate of DNA synthesis in vivo during 12 h in ovaries, fat body, and pericardial cells in B. terrestris queens and workers of different ages. The DNA replication activity was detected on the basis of visualization of incorporated 5-ethynyl-2'-deoxyuridine. DNA synthesis detected in differentiated nurse cells indicated endoreplication of nuclei. The dynamics of mitotic activity varied among different ages and statuses of queens. In 3- to 8-day-old virgin queens, intense mitotic activity was observed in all tissue types investigated. This might be related to the initial phase of oogenesis and the development of the hepato-nephrotic system. In 15- to 20-day-old mated pre-diapause queens, DNA synthesis was exclusively observed in the ovaries, particularly in the germarium and the anterior part of the vitellarium. In 1-year-old queens, replication occurred only in the peritoneal sheath of ovaries and in several cells of the fat body. The similar DNA synthesis patterns in the ovaries of mated pre-diapause queens, ovipositing workers, and non-egg-laying workers show that mitotic activity is related not only to age but also to the stage of ovarian maturation and is relatively independent of caste affiliation.
Keywords: DNA endoreplication; Bombus terrestris; fat body; pericardial cells; EdU detection; ovaries; endopolypoidic nurse cells